Der Transformationsprozeß in den baltischen Staaten: ordnungspolitische Fortschritte und strukturelle Anpassungsprozesse - Klaus Schrader; Claus-Friedrich Laaser (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
In this report the actual state of the economic and structural development, the progress towards establishing a market economy, and the provision of infrastructure in the Baltic states Estonia, Latvia, and Lithuania after five years of independence is analysed. According to a set of relevant theoretical criteria that Estonia has managed to join the club of well established reform countries like the Visegrad countries while Latvia and Lithuania are still lagging behind. With respect to infrastructure all three countries still suffer from the Soviet heritage. Estonia again takes the lead in creating the preconditions for developing the necessary infrastructure facilities.
Keywords: F1; K2; P1; P5; 330; Systemtransformation; Wirtschaftliche Anpassung; Infrastruktur; Privatisierung; Ordnungspolitik; Estland; Lettland; Litauen